Conceptualization of the Scholarship of Engagement in Higher Education: A Ten-Year Retrospective - Lorilee R. Sandmann (Adult Education Research Conference, 2007)
During the past decade the generalized concept of the scholarship of engagement has evolved: once a broad call for higher education to be more responsive to communities, it is now a multifaceted field of responses. Engaged scholarship now has its own distinctive architecture, building on yet differing from traditional scholarship.